Diseases of Roots and Root in Winter Wheat in Uzbekistan - Turdiyeva Dilfuza Tirkashboyevna; Aznabakieva Dilrabo Tursunboevna; Xusanov Baxriddin Baxtiyrjon ugli; Xayitalieva Gulxayo Abdusamad Qizi (International Journal on Orange Technologies, 2021)
The occurrence of root and foot rot diseases on winter wheat fields has been surveyed in 16 districts of six regions of Uzbekistan. Reports about wide occurrence of Fusarium root and foot rots on wheat fields have been confirmed, and causal agents have mostly been identified. For the first time in Uzbekistan severe infection of winter wheat seedlings with common root rot (caused by B. sorokiniana) has been determined on irrigated fields in two districts of Bukhara region. For the first time in the country infection of winter wheat seedlings with a root rot caused by the new for a country incitant of the disease, a fungus Microdochium bolleyi, has been determined in the Andijan region. For the first time an infection of winter wheat seedlings with both the cereal cyst nematode belonging to the Heterodera avenae group and Fusarium sp. has been registered in one field of the Tashkent region.